2020
DOI: 10.1080/0284186x.2020.1830167
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant breast cancer treatment response; tumor size evaluation through different conventional imaging modalities in the NeoDense study

Abstract: Background: Neoadjuvant chemotherapy (NACT) is offered to an increasing number of breast cancer (BC) patients, and comprehensive monitoring of treatment response is of utmost importance. Several imaging modalities are available to follow tumor response, although likely to provide different clinical information. We aimed to examine the association between early radiological response by three conventional imaging modalities and pathological complete response (pCR). Further, we investigated the agreement between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Another study evaluated the response to treatment after NAC with US, MG, and tomosynthesis, and reported that the diagnostic power in predicting pCR after NAC was similar between the three imaging modalities [26].…”
Section: Discussionmentioning
confidence: 99%
“…Another study evaluated the response to treatment after NAC with US, MG, and tomosynthesis, and reported that the diagnostic power in predicting pCR after NAC was similar between the three imaging modalities [26].…”
Section: Discussionmentioning
confidence: 99%
“…At diagnosis, patients eligible for NACT were included in the study following written consent (N = 207), of whom five patients were excluded due to ineligibility (Fig. 1) [25]. All patients with c/pN + pre-NACT were subject to ALND according to clinical routine and the Swedish National Guidelines at the time of study inclusion (Supplementary Material 1).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, most experts consider mammography to be unsuitable for the evaluation of NAC efficacy. In addition, a recent prospective study ( 15 ) compared the size of tumors evaluated by mammography, ultrasound, and tomosynthesis after NAC, and reported the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of mammography as 0.65, 0.81, 0.52, and 0.88, respectively. The agreement rate between mammography and pathological assessment in pCR was only 43%.…”
Section: Evaluation Of the Efficacy Of Mammography On Nac In Breast C...mentioning
confidence: 99%